(untitled) (Journal of Hama University, 2020)
This research aimed to identify the appropriate problem-solving skills needed in the content of the Islamic education book for the fifth grade، to determine the degree of taking into account the problem-solving skills and the degree of their distribution in the exercises، and to clarify the level of inclusion of each problem-solving skills in the exercises. To achieve these goals، a list of problem-solving skills was prepared، and an analysis criterion was prepared in the light، which included (25) sub-criteria representing skills: (Feeling and identifying the problem، gathering information، formulating hypotheses، testing the validity of hypotheses، making decisions، implementing and disseminating the solution). The content of the exercises was analyzed using a descriptive analytical approach based on the method of content analysis. The research found that the content of the training of the book "Islamic Education" scheduled for fifth grade pupils graded low-level problem-solving skills as a whole; (15.42%). It also gave some skills a greater degree of interest than other skills، the skill of testing the validity of hypotheses ranked first (24.13%)، then the skill of drafting hypotheses with interest (20.68%)، then the skill of feeling the problem and identified by Decision-making skills، implementation and dissemination skills ranked fourth (17.24%)، and information-gathering skills (10.34%). The results also showed variation in the care of sub-skills and the frequency of their repetitions، She did not have any training. The research presented some suggestions، including: Making use of (problem solving skills list) in the field of educational curricula by curriculum makers، and conducting training courses for teachers and curriculum authors on the importance of problem solving and practicing different skills.